Studi Rasionalitas Ekonomi pada Mahasiswa Pendidikan IPS FKIP Universitas Mulawarman - Desy Nusriati; Reza; Riyo Riyadi (Jurnal Pendidikan Ekonomi Undiksha, 2022)
The rationality that occurs in the student environment begins to fade along with the many choices given. Students do consumption activities not only based on need, but because of desire. The aims of the study were to (1) determine the economic rationality of the Social Sciences Education FKIP students at Mulawarman University, (2) find out the factors driving and inhibiting the application of economic rationality for students of the Social Sciences Education Department, FKIP Mulawarman University. This research is a phenomenological research with a qualitative approach. The data analysis used is data reduction, data presentation and leverage/drawing conclusions. The results of this study indicate that students of the Social Sciences Department in general have a fairly good economic rationality, students of the Social Sciences Department are able to determine the best course of action. Social Studies Education Department students in their economic behavior make considerations in making decisions. However, there is a side where students of the Social Sciences Education Department are still not rational, namely they are still lacking in making expense records. The category findings are product information, economic action selection, and economic behavior plan. While the factors that drive and inhibit economic rationality are economic conditions, the influence of friends, desires.